2009
DOI: 10.1038/eye.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of traumatic optic neuropathy in the UK

Abstract: Aims The aim of this study is to provide epidemiological data on the incidence, aetiology, management, and visual outcome in traumatic optic neuropathy (TON) in the UK. Methods Patients with TON were identified prospectively by population-based active surveillance through the British Ophthalmic Surveillance Unit over a 2-year period with data obtained from an incident questionnaire and follow-up questionnaire sent to positive reporters. Results Incident and follow-up data were available on 121 and 97 (80%) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
82
2
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 43 publications
10
82
2
3
Order By: Relevance
“…If the days-long period of dendritic pruning after ONC accurately models important aspects of what happens in RGCs of TON patients, then brimonidine may provide enhanced recovery in TON. In support of this potential for recovery, epidemiological studies have reported a portion of untreated TON cases attain 3 or more Snellen lines improvement of visual acuity between presentation and final follow up 42,43. Similarly, growing experimental evidence suggest neuroprotective treatments may increase preservation of vision in glaucoma patients.44- 46 Thus, the present findings support further studies to define the neuroprotective requirements of all RGC subtypes.…”
supporting
confidence: 71%
“…If the days-long period of dendritic pruning after ONC accurately models important aspects of what happens in RGCs of TON patients, then brimonidine may provide enhanced recovery in TON. In support of this potential for recovery, epidemiological studies have reported a portion of untreated TON cases attain 3 or more Snellen lines improvement of visual acuity between presentation and final follow up 42,43. Similarly, growing experimental evidence suggest neuroprotective treatments may increase preservation of vision in glaucoma patients.44- 46 Thus, the present findings support further studies to define the neuroprotective requirements of all RGC subtypes.…”
supporting
confidence: 71%
“…There is no good evidence that either corticosteroids or surgery have any benefit in terms of long-term visual acuity and both may carry the risk of significant morbidity [31,41]. This is reflected in the finding be Lee et al [20 ] of a trend towards conservative management of TON in the UK.…”
Section: Key Pointsmentioning
confidence: 79%
“…Most studies of TON have shown a significant correlation between initial and final visual acuities, patients with direct TON or no light perception at presentation have a poorer prognosis. Lee et al [20 ] found that there was no statistically significant difference in improvement in visual acuity between those patients treated with steroids and/or surgery and the untreated group. There is no good evidence that either corticosteroids or surgery have any benefit in terms of long-term visual acuity and both may carry the risk of significant morbidity [31,41].…”
Section: Key Pointsmentioning
confidence: 97%
See 1 more Smart Citation
“…There were 26 cases of TON in this age group reported over 2 years; thus, the reported incidence was 0.99 per million population. 10,11 This has important implications for increasing awareness among the public and health professionals about the effect of TON on the health of both children and adults.…”
mentioning
confidence: 99%